EFFECTS OF PISOLITHUS TINCTORIUS AND LACCARIA FRATERNA ON THE GROWTH AND MYCORRfflZAL DEVELOPMENT OF PINUSPATULA SEEDLINGS*) - M. SUDHAKARA REDDY; K. NATARAJAN (SEAMEO BIOTROP, 1995)
Vegetative inoculum of Pisolithus tinctorius and Laccariafraterna were inoculated to Pinuspatula seedlings grown in both steam sterilized and unsterilized shola soil. After 4 months of seedling growth, 10 seedlings from each treatment were harvested and various growth parameters were studied. Inoculation of these two fungi resulted in the production of ectomycorrhizas and increase in growth of P. patula seedlings when compared to uninoculated seedlings. Laccariafraterna inoculated seedlings showed more number of mycorrhizas than P. tinctorius inoculated seedlings at the end of one year. Both these fungi poorly colonized the root system in both soil treatments. There was no significant difference between these two fungi in improving the seedling growth in the nursery. Key words: Pisolithus tinctorius/Laccaria fraterna/Pinus patula/Inoculum/Seedlings/Growth.